Gas-PM2.5 partitioning, health risks, and sources of atmospheric PAHs in a northern China city: Impact of domestic heating. (15th November 2022) - Sun, Yuewei; Chen, Jing; Qin, Weihua; Yu, Qing; Xin, Ke; Ai, Jing; Huang, Huiying; Liu, Xingang
Abstract: The diurnal variation, gas-particle partitioning, health risks, and sources of polycyclic aromatic hydrocarbons (PAHs) were investigated in a northern basin city of China in winter, 2020. The mean concentrations of particulate and gaseous PAHs were 87.90 ng m −3 and 69.65 ng m −3, respectively, and their concentrations were considerably enhanced during the domestic heating period. The relationship between the gas-particle partitioning coefficient of PAHs (KP ) and subcooled liquid vapor pressure of PAHs (PL 0 ) indicated organic absorption as the mechanism for this partitioning. However, the dual sorption model confirmed adsorption onto elemental carbon (EC). The health risks indicated by several equivalent parameters showed an important health effect of PAHs, especially of particulate PAHs bound onto PM2.5 during the heating period. Environmentally persistent free radicals (EPFRs) were also studied as an auxiliary parameter to evaluate the health impact of PAHs. According to the diagnostic ratios of PAHs and PMF model results, petroleum volatilization and coal combustion were the dominant sources of particulate PAHs during the non-heating and heating periods, respectively. The source apportionment results can help efficiently control PAHs and their health risks. Graphical abstract: Image 1 Highlights: Adsorption onto EC promoted the gas to particle partitioning of PAHs. The health risks of PAHs were increased during the domestic heating period. Coal combustion was the dominant source of PAHs during the domestic heating period. Petroleum volatilization was the dominant source of PAHs before domestic heating. Environmentally persistent free radicals were closely related to particulate PAHs.